Malposition of a Left-Sided Tunneled Hemodialysis Catheter into the Azygos Vein: A Case Report - Shah, Muhammad Naveed Alam; Ahmed, Fawad; Baloch, Behzad Kaleem (Pakistan Armed Forces Medical Journal, 2026)
Central venous catheterization through the left internal jugular vein poses a rare yet considerable danger of malposition into the azygos vein caused by anatomical angulation and reduced vessel caliber. We introduce the situation of an older woman suffering from chronic kidney disease and heart failure who experienced tunneled hemodialysis catheter placement employing a landmark-guided approach. Initially operational, the catheter was discovered incorrectly positioned in the azygos vein. The position was adjusted under fluoroscopic imaging. This situation highlights the significance of image-assisted insertion in averting such complications and emphasizes the importance of post-procedural imaging, particularly in left-sided catheterization.